PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HIGHER ORDER THINKING SKILL (HOTS) TERINTEGRASI WEB PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Tisrin Maulina Dewi; Fitria Meilina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Abstract: This article reports research about higher-order thinking skills based on web integrated development of students’ worksheets (LKPD) on natural science learning subjects in elementary schools. This product, LKPD, contained a summary of the material and HOTS exercises that were equipped with web access so that it could be used by students in the learning process. The research is developmental research that produced the LKPD product. The research method used descriptive quantitative and qualitative design by involving two design experts, two material experts, six elementary school teachers, and 36 elementary school students. Qualitative data were obtained from observations, interviews, and comments from the validator. Quantitative data were obtained from questionnaires delivered to validators and the users. The research questionnaires were a statement consisting of the feasibility of the media display design and the feasibility of the material. The research results indicated that the validation from the design expert and the material expert teams respectively obtained a score of 84% and 85% with a very feasible category and the results of the teacher's response and the student's test response obtained a score of 84% with very good category. It showed that the developed LKPD product was feasible and could be applied as an alternative to additional teaching materials in the natural science learning process at the elementary school.